TICOM and the Analysis of internal Controls. - Bailey, Andrew D.; Duke, Gordon Leon; Gerlach, James; Ko, Chen-en; Meservy, Rayman D.; Whinston, Andrew B. (The Accounting Review, 1985)
Abstract ABSTRACT: Auditors are charged with the responsibility of evaluating internal control systems. Recent advances in decision support systems indicate that the speed, accuracy, and memory capacity of computers may be used to aid auditors in this task. To test this proposition, a computer-assisted method of designing, analyzing, and evaluating internal control systems, called The Internal Control Model or TICOM, was designed and implemented. The technical manual and the TICOM software are available from the authors. This paper presents the results and conclusions of that project. TICOM is a computer-based analytic tool that aids the auditor first to model the internal control system and then to query the model in order to aid the auditor in evaluating the internal control system. TICOM is based on concepts in artificial intelligence such as knowledge representation and graph simplification. It serves (1) to describe office information systems while emphasizing internal accounting controls and (2) as an aid in control evaluation. It was found that the advantages of TICOM over traditional evaluation methods are that (1) the evaluation can be more rigorous and exhaustive, (2) the documentation of the system can be more thorough because of automated completeness and consistency tests, and (3) the modeler may probe and test controls by using the query-processing portion of TICOM.